Sentience, Awareness, Consciousness - Pokorný, Martin (Organon F, 2012)
The paper starts from a Searlean dilemma – we are bound to view consciousness as ultimately explicable by scientific means, yet science appears to give us no means for explaining the specificity of consciousness – and presents what I see as a plausible though speculative story for avoiding the brunt of the dilemma. The basic idea is (a) that consciousness, or anticipations of it, should be seen as pervasive throughout the biosphere; (b) that the biosphere, following Gerald Edelman, can be seen as the sphere of meta-systems irreducible to purely physical particles and forces; and (c) that it is plausible to view “full waking consciousness” as occurring at a very high level of meta-systematicity; with the conclusion (d) that full waking consciousness is both an expectable outcome of the biogenic forces and, in virtue of how it combines them, a very singular case.
Keywords: sentience; awareness; consciousness; recognition systems; Gerald Edelman